Entrepreneurship and marketing education: time for the road less travelled?. (3rd December 2009) - Stokes, David; Wilson, Nicholas C.
Three dimensions are proposed as a conceptual framework for entrepreneurship education: context, behaviours and process. Entrepreneurship educators have focussed more on the behaviours of entrepreneurs and less on the process of entrepreneurship. In doing so, they have also tended to avoid challenging the context of other disciplines such as marketing. If however we examine important aspects of marketing through the behaviours of entrepreneurs, we find that they do not conform to the standard concepts of marketing as portrayed in widely used learning materials. The increasingly well travelled 'pragmatic' road, which encourages the development of enterprising behaviours and skills, is contrasted with the less travelled 'conceptual' road, where our understanding of the phenomenon of entrepreneurship in contexts such as marketing, is challenged and explained. We suggest that unlike the poet's 'traveler' – who cannot take both roads, entrepreneurship education can benefit most by reaching the fork in the road and taking it.